3D engineered neural co-culture model and neurovascular effects of marine fungi-derived citreohybridonol - Emel Sokullu; İrem Polat; Ferhat Can Özkaya; Mona El-Neketi; Weaam Ebrahim; Misagh Rezapour Sarabi; Gulgun Sengul; Savas Tasoglu (AIP Advances, 2022)
Marine-based biomolecules are emerging metabolites that have gained attention for developing novel biomaterials, drugs, and pharmaceutical in vitro platforms. Here, we developed a 3D engineered neural co-culture model via a 3D prototyped sliding frame-platform for multi-step UV lithography and investigated the neurovascular potential of citreohybridonol in neuroblastoma treatment. Citreohybridonol was isolated from a sponge-derived fungus Penicillium atrovenetum. The model was characterized by Fourier-transform infrared spectroscopy and scanning electron microscopy analysis. Human umbilical cord vein endothelial cells (HUVECs) and neuroblastoma (SH-SY5Y) cell lines were encapsulated in gelatin methacrylate (GelMA) with and without citreohybridonol. The effect of citreohybridonol on the proliferation capacity of cells was assessed via cell viability and immunostaining assays. GelMA and 3D culture characterization indicated that the cells were successfully encapsulated as axenic and mixed with/without citreohybridonol. The cytotoxic test confirmed that the 3D microenvironment was non-toxic for cultural experiments, and it showed the inhibitory effects of citreohybridonol on SH-SY5Y cells and induced the proliferation of HUVECs. Finally, immunohistochemical staining demonstrated that citreohybridonol suppressed SH-SY5Y cells and induced vascularization of HUVECs in mixed 3D cell culture.